A Case Report of Untreatable Complication of Umbilical Hernia in Cirrhosis: A Flood Syndrome - Tan, Christine; Audi Yanto, Theo (The Indonesian Society for Digestive Endoscopy, 2025)
Flood syndrome is a rare, life-threatening complication of end-stage liver disease, characterized by the spontaneous rupture of an umbilical hernia. It frequently presents with sepsis, peritonitis, and bowel incarceration, carrying a high mortality rate. The lack of standardized treatment guidelines and the complexities of advanced liver disease make management particularly challenging. We report a case of a 53-year-old woman with decompensated hepatitis B-related cirrhosis (Child-Pugh Class C, MELD score of 26) and refractory ascites, who developed Flood syndrome. She presented with a ruptured umbilical hernia leaking ascitic fluid, accompanied by sepsis, diabetic ketoacidosis, acute kidney injury, and hypoalbuminemia. Surgical intervention was deemed high-risk, and conservative management was undertaken, focusing on infection control, wound care, and medical stabilization of her comorbidities. Despite a multidisciplinary approach, the patient succumbed to the cumulative effects of her advanced disease and associated complications. This case highlights the complexities of managing Flood syndrome, particularly in patients with advanced liver disease. The absence of standardized treatment protocols necessitates a multidisciplinary, individualized approach. Key considerations include managing ascites, preventing infection, optimizing glycaemic control, and carefully evaluating the risks of surgical intervention. This case report illustrates the clinical course, management challenges, and outcomes of Flood syndrome in a patient with advanced cirrhosis, in order to highlight key considerations for clinicians and underscore the urgent need for further research to establish evidence-based guidelines for managing this rare but life-threatening condition.